1997
DOI: 10.1161/01.cir.96.2.683
|View full text |Cite
|
Sign up to set email alerts
|

High-Energy Defibrillation Increases the Severity of Postresuscitation Myocardial Dysfunction

Abstract: The severity of postresuscitation myocardial dysfunction is related, at least in part, to the magnitude of the electrical energy of the delivered shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(107 citation statements)
references
References 34 publications
2
100
0
5
Order By: Relevance
“…However, many defibrillation attempts are futile [11,12]. The consequences are longer CPR interruptions to charge the defibrillator and potential damage to the myocardium caused by the shock; both of these factors compromise the survival of the patient [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, many defibrillation attempts are futile [11,12]. The consequences are longer CPR interruptions to charge the defibrillator and potential damage to the myocardium caused by the shock; both of these factors compromise the survival of the patient [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous clinical and pre-clinical studies showed that the ICD shocks may induce myocardial injury and shocks with a higher output can cause more severe myocardial damage than those with a lower output. [13][14][15] If the DFT testing is not performed, it is hard to be convinced that the lower energy output would work effectively. In the present study, we found that the mean DFT was 11.6 ± 9.24J using modern era devices that performed the measurements with step-bystep DFT testing, and in almost half of the study patients (49.4%), the VF was terminated by a low energy (5J).…”
Section: Discussionmentioning
confidence: 99%
“…9) The cause of increased risk may be postulated that the negative inotropic consequences of the shock itself could increase the risk of death, especially when the patient receives multiple shocks due to oversensing or in response to ongoing supraventricular tachycardia. [10][11][12][13] Thus, effective strategies to reduce ICD shocks are desirable. Antiarrhythmic medication is frequently administered in patients with an ICD.…”
Section: Discussionmentioning
confidence: 99%